A Systematic Review of Diagnostic Approaches for Pediatric Epilepsy: An Evidence-Based Framework from Clinical Assessment to Precision Medicine - Raras Windaswara; Yaffie Noor Rochim (The International Journal of Medical Science and Health Research, 2025)
Introduction: Pediatric epilepsy is a common and heterogeneous neurological disorder, and an accurate, timely diagnosis is paramount for guiding treatment, determining prognosis, and improving long-term outcomes. The diagnostic paradigm has evolved from a descriptive, seizure-based classification to a comprehensive, multi-axial framework focused on establishing an underlying etiology. This systematic review synthesizes the current evidence on the diagnostic approaches for pediatric epilepsy, from foundational clinical evaluation to advanced molecular and neuroimaging techniques. Methods: A systematic search of PubMed, Embase, and the Cochrane Library was conducted to identify systematic reviews, meta-analyses, cohort studies, and clinical guidelines published on the diagnosis of epilepsy in children (age ≤ 18 years). Studies were selected based on their evaluation of the utility, diagnostic yield, predictive value, and clinical impact of various diagnostic modalities. Data were extracted and synthesized according to a tiered diagnostic pathway. Results: The diagnostic process begins with a meticulous clinical history and neurological examination, which remain the cornerstone for differentiating epileptic seizures from paroxysmal non-epileptic events (PNEEs). Misdiagnosis remains a significant challenge, with up to 39% of children referred to tertiary centers for refractory epilepsy ultimately found not to have the condition. Electroencephalography (EEG) is the principal ancillary test, with an initial diagnostic yield of approximately 52%; this can be enhanced by provocation techniques and sleep deprivation. Long-term video-EEG monitoring (VEM) is the gold standard for resolving diagnostic uncertainty, achieving a definitive diagnosis in over 75% of complex cases. However, EEG interpretation is subject to significant inter-observer variability. Structural neuroimaging with Magnetic Resonance Imaging (MRI) identifies an epileptogenic lesion in 33-44% of children, a yield that is substantially increased by advanced post-processing techniques in MRI-negative cases. Functional neuroimaging (PET, SPECT, MEG) and genetic testing represent the frontier of etiological diagnosis. Magnetoencephalography (MEG) can localize epileptogenic foci in MRI-negative patients with high accuracy, guiding successful surgical intervention. Genetic testing, particularly exome and genome sequencing, provides the highest diagnostic yield, identifying a causative variant in 25-48% of cases, especially in infants with early-onset and severe epilepsies. A genetic diagnosis directly impacts clinical management in up to 85% of diagnosed children. Economic analyses demonstrate that early, comprehensive genetic testing is more cost-effective than traditional, protracted sequential investigations. Discussion: The evidence supports a paradigm shift away from a rigid, sequential diagnostic model toward a flexible, phenotype-driven approach. For severe, early-onset epilepsies, rapid exome or genome sequencing should be considered a first- or second-line investigation rather than a last resort. The integration of multimodal data—clinical, electrophysiological, imaging, and genomic—is essential for accurate diagnosis, particularly in drug-resistant and MRI-negative epilepsy. Conclusion: The modern diagnostic evaluation of pediatric epilepsy is a multi-faceted process that leverages a synergistic combination of clinical acumen and advanced technology. An accurate and timely etiological diagnosis is not merely an academic exercise but a critical intervention that directly informs precision therapy, improves seizure control, and fundamentally alters the life course for children with epilepsy and their families.